Reaktualisaasi Konsep Kafa’ah Dalam Bingkai Perubahan Sosial Di Kabupaten Lamongan - Muh. Makhrus Ali Ridho; Ja’far Shodiq (Institut Ilmu Keislaman Zainul Hasan Genggong, 2021)
This research aims to show the change of kafa’ah concept on the social transformation in Lamongan District. Kafa’ah is equality between husband and wife in a family on certain compont. kafa’ah is preventife strategy to minimize difference between husband and wife. This difference can to be a conflict in a family. On islamic law (Hanafi school), componts of Kafa’ah are; cognation, Islam, independence, Propert and piety. But, the social change motivate to reactualisation of kafa’ah concept. The this componts in Lamongan District are; cognation, education, piety, profession and salary.